(3eaQMI GdCfGe aj JCSjS HjJ Gddg GdMQGes - (3GdcGTGfj, , GdcGTGfj, Rjf GdYGHOjf Hf fhQ GdOjf Hf eQGO, Js ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj LYd GdHjJ GdMQGe ef LHGd NTfI(B... (3GdaUd GdChd aj SHH SbhW GdcYHI GdeYXeI (B... (3hcjajI HfGAgG, GdaUd GdKGfj aj YdI HfGA GdcYHI aj GdCQV hHOA GdWhGa HgGs
(3BNQgG (B:s
(3BNQgG(B: (3hCeG GdTHjcI agj CjVG LHGfI YXjeI bO Oaf ajgG LeGYI cKjQI ef GdfGS hdjS ajgG ef eTGgjQ GdbHhQ YfOfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI, L (B21: 233s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis